Reversible Inactivation of the Dorsal Raphe Nucleus Increases Morphine-Induced Antinociception in Tolerated but not in Nontolerated Rats - Sarihi, A.; Heshmatian, B.; Pahlevani, P.; Komaki, A.; Haghparast, A. (Нейрофизиология, 2015)
We examined possible effects of the state of the dorsal raphe nucleus (DRN) on morphineinduced antinociception in morphine-tolerated and nontolerated rats. Stereotaxically,
lidocaine (2%) was applied to the DRN for its reversible inactivation. On the test day, all
animals received 10 mg/kg morphine 10 min before the tail-flick test (induction of thermal
acute pain), and the maximum antinociceptive effect (MPE) was measured. In the morphinetolerated group, animals preliminarily received everyday introductions of 20 mg/kg morphine
for four consecutive days. There was a significant increase in the MPE (%) in the lidocainetreated group (with inactivation of the DRN) compared to the control group. However, there
was no significant difference in morphine-induced antinociception between the saline- and
lidocaine-treated groups. Nonetheless, the antinociceptive responses to morphine (MPE) in
morphine-tolerated rats were more significant in animals treated with lidocaine compared
to the control group. Our results suggest that lack of GABA in the locus coeruleus, which
follows inhibition of serotonin release in the DRN during ablation, may cause adrenergic cellinduced analgesic effects. Ми досліджували можливі впливи стану nucl. raphe dorsalis (DRN) на індуковане морфіном знеболення у щурів, толерантних щодо морфіну. З використанням стереотаксичної техніки лідокаїн (2 %) уводили в DRN, що зумовлювало
оборотну інактивацію останнього. В день тестування тваринам уводили морфін за 10 хв перед тестом відсмикування
хвоста (індукції гострого термального болю) та розраховували максимальний антиноцицептивний ефект (МАЕ%). У
групі тварин з толерантністю до морфіну в три послідовні
доби отримували попередні ін’єкції останнього. В групі з
ін’єкціями лідокаїну (з інактивацією DRN) значення МАЕ%
були істотно збільшеними порівняно з контролем. Не спостерігалося, проте, істотних відмінностей між рівнями індукованого знеболення в групах тварин, котрим уводили
фізрозчин та лідокаїн. У той же час антиноцицептивні відповіді на введення морфіну (МАЕ%) у тварин із толерантністю до морфіну були істотнішими у тих щурів, котрим
уводили лідокаїн, ніж у контрольних. Наші результати дозволяють думати, що дефіцит ГАМК у locus coeruleus після гальмування вивільнення серотоніну в DRN внаслідок
функціонального виключення останнього може зумовлювати аналгезивні ефекти, опосередковані адренергічними клітинами.